Performance of Beeswax and Ricebran-Wax Coating on Weight Loss of Local Indonesian Fruits: Kirana Banana, Gedong Mango, and Pontianak Orange - Nugrahani, Ratri Ariatmi; Hendrawati, Tri Yuni; Hasyim, Ummul Habibah; Hakim, Rusnia Junita (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2024)
Bananas, mangoes, and oranges are fruit commodities that are quite potent and have a promising export market share. The shelf life of the fruit is not long and causes physical-chemical damage to the fruit, one way that can be done in post-harvest handling of the fruit is by using the wax method. This study used types of wax, namely beeswax and rice bran wax. The purpose of this study was to determine the effect of beeswax coating on fruit weight loss, to determine the effect of rice bran wax concentration on the characteristics of rice bran wax coating and fruit weight loss, determine the effect of storage time of bananas, mangoes, and oranges on fruit weight loss. The independent variables in this study included rice bran wax concentration (6;9;12;15;18)% and fruit storage time of 3 weeks, while the dependent variables in this study included pH, density (gr/ml), viscosity (seconds), mango fruit weight loss ( %). The procedures in this study include the manufacture of beeswax coating, and rice bran coating, analysis of characteristics of beeswax coating and rice bran wax coating, and analysis of weight loss of bananas, mangoes and oranges after coating. The results of the analysis of the characteristics of rice bran wax coating (pH, density, viscosity) on the concentration of rice bran wax (6; 9; 12; 15; 18)% showed that the pH showed a downward trend with a pH value of 9.33; 9.22; 9.21; 9.18 and 8.95, the density showed a tendency to increase with a density value of 1.018; 1.021; 1.022; 1.023; and 1.026 gr/ml, the viscosity showed a tendency to increase with a value of 8.85; 8.2; 8.3; 8.43; 8.56 seconds. Characteristics of Beeswax Coating 12% resulted in a pH of 9.19, a density of 1.019 g/mL, and a viscosity of 8.3 seconds. The smallest weight loss of mangoes and oranges for 3 weeks was fruit coated with 12% beeswax coating, and the smallest weight loss for bananas for 3 weeks was fruit coated with 12% rice bran wax coating.